2023
DOI: 10.1002/ohn.362
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hearing Loss on Health Care Access During the COVID‐19 Pandemic

Abstract: Individuals with hearing loss are at increased risk of having poor access to health care compared with hearing peers. The impact of the COVID‐19 pandemic on health care access for adults with hearing loss in the United States was investigated through weighted analyses of the 2021 National Health Interview Survey. The association of hearing loss and disruptions to health care use during the pandemic was examined using multivariable logistic regression controlling for demographic characteristics including sex, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Participants with ADL or communication disabilities experienced the greatest number of barriers, with as many as three-quarters experiencing 3 or more barriers in the past 3 years, suggesting that these groups may require the most support. The preponderance of access barriers experienced was consistent with that in other studies that found disparities in general health care access for people with disabilities . Thus, disparities in gynecological cancer screenings and contraceptive use may be due to structural barriers to care.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Participants with ADL or communication disabilities experienced the greatest number of barriers, with as many as three-quarters experiencing 3 or more barriers in the past 3 years, suggesting that these groups may require the most support. The preponderance of access barriers experienced was consistent with that in other studies that found disparities in general health care access for people with disabilities . Thus, disparities in gynecological cancer screenings and contraceptive use may be due to structural barriers to care.…”
Section: Discussionsupporting
confidence: 86%
“…The preponderance of access barriers experienced was consistent with that in other studies that found disparities in general health care access for people with disabilities. 32 , 33 , 34 Thus, disparities in gynecological cancer screenings and contraceptive use may be due to structural barriers to care. Future research needs to examine access to other RH services, such as screening for sexually transmitted infections (STIs) and abortion care, which were not examined in this study, although we did find that people with disabilities are more likely to consider SMA than people without disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Multiple studies have found that hearing loss may adversely affect mobility and increase the risk of falls in the elderly, [5][6][7][8] which may in turn lead to poor outcomes such as decreased access to health care and increased mortality. 9,10 Limited physical mobility is common for patients of all ages in the United States 11 and is associated with poor performance of daily activities, depressive symptoms, and diminished quality of life. [11][12][13] The association between hearing health and physical mobility remains under investigation, particularly among younger adults as there have been no large-scale studies of this association that have included US adults of all ages.…”
mentioning
confidence: 99%
“…From a public health perspective, hearing loss is a modifiable risk factor for several adverse outcomes through the use of hearing aids or other hearing augmentation devices 2‐4 . Multiple studies have found that hearing loss may adversely affect mobility and increase the risk of falls in the elderly, 5‐8 which may in turn lead to poor outcomes such as decreased access to health care and increased mortality 9,10 . Limited physical mobility is common for patients of all ages in the United States 11 and is associated with poor performance of daily activities, depressive symptoms, and diminished quality of life 11‐13 …”
mentioning
confidence: 99%